THE EFFECT OF EXCHANGE RATES, INTEREST RATES, AND PROFITABILITY ON BANKING STOCK PRICES ON THE IDX FOR THE 2020-2024 PERIOD - Detak Prapanca; Shofi Maulana Ardiansyah; Herlinda Maya Kumala Sari; Rita Ambarwati Sukmono (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study aims to analyze the effects of exchange rates, interest rates, and profitability on stock prices in the banking sector on the Indonesia Stock Exchange for the period 2020–2024. Method: The subjects of this study are banking companies listed on the IDX, with a sample of 7 companies selected through purposive sampling. This study employs a quantitative approach using data collection methods in the form of financial statement documentation. The data sources used are secondary data obtained from company financial statements and related publications. Data analysis techniques utilize multiple linear regression with the assistance of SPSS software, as well as through the stages of classical assumption testing and hypothesis testing. Results: The results of the study indicate that (1) the exchange rate have a positive significant effect on the price of banking stocks; (2) interest rates have a negative significant effect on the price of banking stocks; (3) profitability has a positif significant effect on the price of banking stocks; (4) simultaneously, the three variables can explain 23.5% of the variation in stock prices; (5) macroeconomic and internal company factors, especially profitability, have a more equal influence on share prices; (6) there are other factors outside the research model that also influence banking stock prices. Novelty: This study analyzes the combined effects of exchange rates, interest rates, and profitability on banking stock prices in Indonesia using data from the 2020–2024 period.